Bevacizumab-associated Bowel Microperforation in a Patient With Neuroblastoma. Issue 6 (August 2018) - Glincher, Rachel; Price, Anita P.; LaQuaglia, Michael P.; Kushner, Brian H.; Modak, Shakeel
Abstract : The antivascular endothelial growth factor antibody, bevacizumab, is effective against several malignancies in adults but unproven in pediatric oncology. In early phase pediatric studies toxicities were similar to those in adults. Bowel perforation in adults is a rare but serious toxicity, but has not been hitherto reported in children. A 5-year-old boy with chemoresistant neuroblastoma treated with bevacizumab plus radioimmunotherapy developed acute abdominal pain. Computed tomography scan showed free abdominal air and pneumatosis coli. Emergency laparotomy and bowel diversion were performed leading to complete recovery and timely continuation of antineuroblastoma therapy. Early recognition and rapid intervention can prevent a catastrophic outcome in bevacizumab-related bowel perforation.